Rice Husk Ash and Quarry Waste Mixture as Shell Material in Earth Dam: Experimental and Numerical Investigations - Ambarakonda P.; Mohanty S.; Shaik R. (My University, 2025)
In the present study an attempt has been made to propose the application of rice husk ash (RHA), by strengthening it using quarry waste (QW) as additive material in varying percentages of weight. Geotechnical properties of RHA and its combinations with quarry waste (RQ10, RQ20, RQ30, RQ40, RQ50 and RQ60) have been studied by performing grain size analysis, specific gravity, compaction, permeability and triaxial tests. The maximum increase in density, shear strength of RHA upon the addition of quarry waste was observed to be about 45.6% and 39%, respectively. The permeability of RHA, RQ mixes was found to be in fine sand range and hence their application as shell material in earth dam was proposed. The combination RQ50, with equal amounts of RHA and QW was found to exhibit maximum shear strength and was thus considered as the optimum mix. To assess the suitability of RQ50 as shell material in earth dam, numerical analysis of dam system was performed under seismic loading using FEM software Plaxis2D. The seismic behavior of dam system under the application of Nepal input motion was found satisfactory showing high shear resistance and safety against liquefaction. From the outcomes of laboratory and numerical investigations, RHA-QW mixture has been considered as a promising material to be used in earth dam enabling the bulk utilization of both the waste materials. © 2019, Springer Nature Switzerland AG.